Style for actors : a handbook for moving beyond realism - Barton, Robert, 1945- (Routledge, 2021)
"Style For Actors is an award-winning handbook and the definitive guide to roles in historical drama. Anyone who has ever struggled with capes, fans, swords, doublets and crinolines should make this third edition their constant companion. The past is a foreign country, and this outstanding book is concerned with exploring it from the actor's point of view. Specific guides to each major period give readers a clear map to discover a range from Greek, Elizabethan, Restoration and Georgian theatre to more contemporary stylings, including Futurism, Surrealism and Postmodernism. New material in this edition covers commedia dell'arte and non-Western forms of theatre, theatrical fusion, and developments in musicals and Shakespeare. The book's references, images, resource lists and examples have all been updated to support today's diverse performers. Robert Barton takes great care to present the actor with the roles and genres that will most commonly confront them. Containing a huge resource of nearly 150 exercises, suggestions for scene study and applications not only for theatrical performance but also for stylistic challenges in the reader's own offstage life, this book is an invaluable resource for students and practitioners of Acting and Drama"--